Pengaruh Suhu Pemanas Pada Mesin Pengering Cocopeat Tipe Rotary Dryer - Unggul Satria Jati; Nur Akhlis Sarihidaya Laksana; Dian Prabowo; Nur Indah Wardani; Prastiyo Kurniyanto; Bryan Dwi Fauzi (P3M Politeknik Negeri Cilacap, 2025)
The rotary dryer is a machine designed to simplify the cocopeat drying process. The current process still relies on sunlight; this drying process has the drawback of longer drying times and uncontrolled moisture content. The maximum moisture content of the cocopeat must be 15%. This research method is an experiment using several parameters: a drum speed of 6 rpm, heating temperatures of 600°C, 900°C, and 1300°C, with varying drying times of 120 and 150 minutes. The drying process at a temperature of 600 °C resulted in a decrease in humidity efficiency of up to 56.7% with a water content value of 23.8% in 150 minutes and a mass of 3.7 kg. Meanwhile, for drying at a temperature of 1300 °C, the best reduction in efficiency was obtained compared to the previous temperature, a decrease in water content of up to 84% with a water content value of 8.55 and a mass of 2.7 kg using a time of 150 minutes.